Oral diseases in patients infected with HIV - Dominika Magdalena Egierska; Michał Perszke; Aleksy Grzelewski; Kamil Cieślak; Oskar Tokarczuk; Witold Świenc; Miłosz Berliński (Kazimierz Wielki University, 2022)
Introduction: In recent years, more and more people have become infected with Human Immunodeficiency Virus. Of great importance in the course of HIV infection are symptoms and diseases, which often occurs in the oral cavity with a corresponding decrease in lymphocytes. Aim: The aim of the study was the study was to present the most common oral diseases in patients infected with Human Immunodeficiency Virus like hairy leukoplakia, Candidas, angular cheilitis, Linear Gingival Erythema, Herpesviridae virus infections, ulcerative lesions or xerostomia. Description: Clinicians should pay attention to oral manifestation of HIV infections because it may speed up the diagnostics process and may allow better control of the course of the infection. Hairy leukoplakia related to EBV is a marker of HIV on the side border of the tongue and appears as a hyperkeratotic stripes. Candidiasis may occur in many forms as acute pseudomembranous candidiasis, acute erythematous candidiasis, hyperplastic candidiasis or Median Rhomboid Glossitis. The most common fungus is Candida albicans but there may also be Candida krusei, Candida glabrata or Candida tropicalis. Another disease is Angular Cheilitis which is an inflammatory process localized in the commissure of the labia and can be caused by vitamin B deficiency, Candida, Staphylococcus or Streptococcus infection. Linear Gingival Erythema is a red linear lesion on the gingival margin infiltrated by polynuclear leukocytes and plasma cells. Patients with HIV also present Herpesviridae infections symptoms, ulcerations. Summary: This review shows that HIV/AIDS patients should be monitored for oral manifestation of the HIV infection and weakened immune system. Diseases described in this study are reliable markers of the HIV infection and clinicians should pay attention to them to monitor the course of primary infection.